Analisis Manajemen Risiko pada UMKM “ES KEPAL MILO” - Arfiansyah, Bilal (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to trace the history and development of UMKM "ES KEPAL MILO" in Indonesia. As well as identifying and analyzing the management applied by the "UMKM" business actors. In marketing Es Kepal Milo in the modern era like today.